2015
DOI: 10.1021/acs.est.5b01875
|View full text |Cite
|
Sign up to set email alerts
|

Acetonitrile and N-Chloroacetamide Formation from the Reaction of Acetaldehyde and Monochloramine

Abstract: Nitriles and amides are two classes of nitrogenous disinfection byproducts (DBPs) associated with chloramination that are more cytotoxic and genotoxic than regulated DBPs. Monochloramine reacts with acetaldehyde, a common ozone and free chlorine disinfection byproduct, to form 1-(chloroamino)ethanol. Equilibrium (K1) and forward and reverse rate (k1,k-1) constants for the reaction between initial reactants and 1-(chloroamino)ethanol were determined between 2 and 30 °C. Activation energies for k1 and k-1 were 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 31 publications
1
49
1
Order By: Relevance
“…T his result is consistent with previous reports that the formation of N-chloraldimines from the chloramination of aldehydes in aqueous solutions is very slow. 27,38 T herefore, N-chloroisobutyraldimine was produced in anhydrous conditions;…”
Section: Resultsmentioning
confidence: 99%
“…T his result is consistent with previous reports that the formation of N-chloraldimines from the chloramination of aldehydes in aqueous solutions is very slow. 27,38 T herefore, N-chloroisobutyraldimine was produced in anhydrous conditions;…”
Section: Resultsmentioning
confidence: 99%
“…A major question that needs further investigation is how these volatile nitrogenous compounds are formed and whether their direct analysis by SIFT-MS in the headspace may offer insight into the reactions of NaOCl with proteins and amino acids. One possible explanation for the formation of CH 3 CN is by the reaction of NaOCl with aldehydes and monochloramines, which has previously been investigated using solid phase microextraction (SPME) and GC-MS [ 46 ]. Note that acetaldehyde is present in the headspace of our samples.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was shown that ZVI-NPs entrapped in sol-gel matrices can be used as effective heterogeneous catalysts for reductive dehalogenation reactions (RDH) of halo-acetic acids [31]. The high yields and the stability of the catalyst suggest its plausible use for the reduction of the more toxic and very abundant chloroacetamides family of pollutants [2,[32][33][34]. To the best of our knowledge, there has been no attempt to date to utilize ZVI-NPs as a catalyst in the reductive dehalogenation of chloroacetamides.…”
Section: Of 17mentioning
confidence: 99%
“…More than half a century ago it was proposed to study each halogenated compound independently of its homologue hydrocarbon series [1]. While there are number of halogenated pollutants that are monitored by the health authorities, e.g., halo-acetic acids, others which appear on the EPA's (United States Environmental Protection Agency) contaminant candidate list await proper directives and legislation, e.g., halo-acetamides which are formed during chlorination of drinking water [2]. Halo-organic compounds can be reduced electro-chemically [3,4], photo-chemically [5], radiolytically [6], and by a variety of reducing agents [7].…”
Section: Introductionmentioning
confidence: 99%